Language and deontology in social ontology - Forgione, Luca (Mechane, 2024)
In his book Documentality, Ferraris imagines a wedding scenario where all participants have Alzheimer. The ceremony proceeds as normal, and by its end, a new husband and wife exist. However, the next morning, the spouses forget everything. This scenario underscores the importance of writing in Ferraris’ theory. A recorded document, such as a marriage certificate, could confirm their marriage. Ferraris’ approach to documentality and social ontology illustrates that if the discovery of this document occurred after the death of the spouses, it would confirm a real marriage in which the spouses were unaware they had been married (§§ 1-2). The central question addressed in this paper is: Can documentation replace the deontic and constitutive functions of language? Searle’s philosophy of society, through his philosophy of language and mind, will be examined to discuss how language creates social objects via collective intentionality (§§ 3-6). It is precisely language, with its inherent deontology, that enables the existence of real marriages even without recorded evidence (§ 7-9).